Genome‐wide analysis of somatic copy number alterations and chromosomal breakages in osteosarcoma. Issue 4 (25th May 2017) - Smida, Jan; Xu, Hongen; Zhang, Yanping; Baumhoer, Daniel; Ribi, Sebastian; Kovac, Michal; von Luettichau, Irene; Bielack, Stefan; O'Leary, Valerie B.; Leib‐Mösch, Christine; Frishman, Dmitrij; Nathrath, Michaela
Abstract : Osteosarcoma (OS) is the most common primary malignant bone tumor in children and adolescents. It is characterized by highly complex karyotypes with structural and numerical chromosomal alterations. The observed OS‐specific characteristics in localization and frequencies of chromosomal breakages strongly implicate a specific set of responsible driver genes or a specific mechanism of fragility induction. In this study, a comprehensive assessment of somatic copy number alterations (SCNAs) was performed in 160 OS samples using whole‐genome CytoScan High Density arrays (Affymetrix, Santa Clara, CA). Genes or regions frequently targeted by SCNAs were identified. Breakage analysis revealed OS specific unstable regions in which well‐known OS tumor suppressor genes, including TP53, RB1, WWOX, DLG2 and LSAMP are located. Certain genomic features, such as transposable elements and non‐B DNA‐forming motifs were found to be significantly enriched in the vicinity of chromosomal breakage sites. A complex breakage pattern—chromothripsis—has been suggested as a widespread phenomenon in OS. It was further demonstrated that hyperploidy and in particular chromothripsis were strongly correlated with OS patient clinical outcome. The revealed OS‐specific fragility pattern provides novel clues for understanding the biology of OS. Abstract : What's new? Osteosarcoma (OS) is characterized by highly complex karyotypes with structural and numerical chromosomal alterations. The observed OS‐specific characteristics in localization and frequencies of chromosomal breakages implicate a specific set of responsible driver genes or specific mechanism of fragility induction. Here, a comprehensive assessment of somatic copy number alterations (SCNAs) was performed in 160 OS samples. Breakage analysis revealed OS specific unstable regions in which well‐known OS tumor suppressor genes, including TP53, RB1, WWOX, DLG2 and LSAMP are located. A complex breakage pattern–chromothripsis–was suggested as a widespread phenomenon in OS and found to be predictive of patient clinical outcome.